Kant's Legacy: Exploring Borders, Races, and Gender in His Philosophy - Adeoye, Moses Adeleke (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
Immanuel Kant's philosophy, celebrated for its universalist ethics, harbors a shocking paradox: his groundbreaking ideas on autonomy and cosmopolitanism coexist with deeply Eurocentric, racist, and patriarchal views. This tension raises urgent questions about the applicability of Kantian principles in contemporary debates on borders, race, and gender. This study critically examines Kant's legacy, interrogating how his moral and political frameworks, while foundational, reinforce hierarchies that marginalize non-Europeans, women, and migrants. The research objectives are threefold: (1) to analyze Kant's contradictions between universalism and exclusionary practices, (2) to assess the implications of his racial and gendered hierarchies for modern social justice movements, and (3) to explore pathways for reclaiming Kantian ethics inclusively. Using a systematic literature review of peer-reviewed works (1990–2024), the study synthesizes critiques from critical race theory, feminist philosophy, and postcolonial studies. Key findings reveal that Kant's racial theories justified colonial oppression, his gender binaries perpetuated patriarchal norms, and his cosmopolitanism neglected border violence. However, his emphasis on human dignity offers a redeemable framework for rethinking global justice. The study contributes by bridging Kantian scholarship with intersectional critiques, proposing a revised ethics that confronts historical biases while retaining universalist aspirations. By exposing these contradictions, the paper urges philosophers to reckon with Kant's legacy—not to discard it, but to transform it into a tool for equity.